Outcomes of open artificial urinary sphincter in women with stress urinary incontinence: long-term follow up. (September 2019) - Tricard, Thibault; Jochum, Floriane; Bergerat, Sébastien; Munier, Pierre; Schroeder, Alice; Saussine, Christian
Background: The aim of this study was to report the outcomes of artificial urinary sphincter (AUS) in women with stress urinary incontinence (SUI) resulting from intrinsic sphincter deficiency after a follow up of 10 years. Methods: The charts of female patients with moderate-to-severe SUI who underwent open AUS implantation between November 1994 and April 2007 were reviewed retrospectively. All patients were operated on by a single experienced surgeon through an open retropubic approach with systematic bladder incision. Primary endpoint was postoperative continence categorized as complete continence (no pads used), improved incontinence, or unchanged incontinence. Results: A total of 63 women (mean age: 58 years, range: 17–82) underwent open AUS implantation. There were seven (11.1%) intraoperative complications. At the last follow up, 26 (41.3%) initial AUSs remained in situ and 21 (33.3%) patients had at least one revision or reimplantation. Of these 47 patients (74.6%), 35 (74.5%) were fully continent, 3 (6.4%) had improved incontinence, and 9 (19.1%) had unchanged incontinence. A total of 20 patients (31.7%) experienced postoperative complications, but only 2 (3.2%) were Clavien ⩾3. After a median follow up of 14 ± 6 years, 20 (31.7%) explantations and 29 (46%) revisions occurred. The average time without explantation or revision was 11.6 and 9 years, respectively. Conclusions: In our experience, AUS is a good option for women with moderate to severe SUI, with good long-term outcomes.